Society and Behavior: Sociology 222 - O’Brien, Jodi (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course fulfills the requirements for Phase II of the Core, "The Person in Society". The main goal of this course is for you understand how we become social creatures and how, through our everyday interactions with one another, we make and re-make ourselves and our social worlds. One important implication of the ideas covered in this course is that if we understand how it is that we participate in the construction of our own realities, then we can take a more active and purposeful approach toward making this the sort of world in which we want to live.